Cytotoxic effect of Eleutherococcus trifoliatus (L.) S.Y. Hu stem bark extracts on Gastric, Lung, and Hepatocellular cancer cells - Bui Thi Kim Ly; Nguyen Quan; Hoang Thanh Chi (International Journal of Secondary Metabolite)
Eleutherococcus trifoliatus is a popular medicinal species used in Asian folk medicine with many uses in treating human diseases. Scientific research on this plant has been limited, but some scientific publications have described this herb's anti-inflammatory, antibacterial, antioxidant, and anti-cancer activities. Although it is a frequently used part of traditional medicine, current scientific evidence on the biological activities of E. trifoliatus stem bark is still lacking. By performing chemical reactions, free radical scavenging experiments, toxicity experiments on brine shrimp, and cytotoxicity tests using MTT dye, the study has shown the diversity in the metabolic composition of E. trifoliatus stem bark as well as the antioxidant capacity and safety of the total extract. The anticancer effect of the total extract was investigated and indicated the dramatical ability to inhibit the cell growth of liver cancer HCC-J5 cells (IC50 = 19.35 ± 4.89 µg/mL), lung cancer cells A549 (IC50 = 5.34 ± 1.62 µg/mL) and gastric cancer cells AGS (IC50 = 0.22 ± 0.20 µg/mL); the selectivity in effects was also observed. The chloroform fraction had the most potential to be further exploited in the direction of inhibiting cancer cells.